Inovasi Metode Pembelajaran di Pesantren: Menggabungkan Tradisi dan Modernitas - Sunar, Sunar; Priyanto, Priyanto; Jumingan, Jumingan; Akbar, Muhammad Aidil (TSAQOFAH, 2026)
Pesantren education in Indonesia plays a fundamental role in the development of Islamic education, yet it still faces the challenges of modernity, including the stigma that its educational system is outdated. This study aims to identify and analyze the forms of reform undertaken in pesantren and their impact on educational quality. A qualitative approach with a literature study method was employed, drawing on relevant journal articles and books on pesantren educational reform. The findings indicate that reform in pesantren education is crucial to addressing contemporary challenges, particularly through curriculum integration that is more aligned with current societal needs and the modernization of educational processes to enhance quality and graduate competitiveness. The results also show that government support and community participation are key factors in driving educational innovation in pesantren, while the involvement of santri in the reform process strengthens the relevance and acceptance of the changes implemented. This study affirms that pesantren educational reform requires sustained synergy among stakeholders to ensure the quality, relevance, and sustainability of pesantren education amid ongoing social change.